Threatened and recently extinct vertebrates of the world a biogeographic approach - Richardson, Matthew 1966- (Cambridge University Press, 2023)
Habitat loss and degradation are currently the main anthropogenic causes of species extinctions. The root cause is human overpopulation. This unique volume provides, for the very first time, a comprehensive overview of all threatened and recently extinct mammals, birds, reptiles, amphibians, and fishes within the context of their locations and habitats. The approach takes a systematic examination of each biogeographic realm and region of the world, both terrestrial and marine, but with a particular emphasis on geographic features such as mountains, islands, and coral reefs. It reveals patterns useful in biodiversity conservation, helps to put it all into perspective, and ultimately serves as both a baseline from which to compare subsequent developments as well as a standardization of the way threatened species are studied